THE BENEFITS AND CHALLENGES OF FLIPPED LEARNING IN ENGLISH LANGUAGE IN PRIMARY EDUCATION - Sodiqova , O (Educational Research in Universal Sciences, 2024)
The landscape of education is continually evolving, with educators exploring innovative methods to enhance learning experiences. One such approach that has gained attention is flipped learning, a pedagogical model that flips the traditional classroom dynamic. This article delves into the benefits and challenges of implementing flipped learning specifically in the context of English language education at the primary level.